CAPACITY BUILDING ORGANISASI POSKESTREN MAMBA’UL HUDA - Rofi'i, Abdul Halim; Addury, Multazam Mansyur (Khidmatan, 2021)
In the form of empowerment of facilities and infrastructure in Islamic boarding schools, Mamba'ul Huda Islamic Boarding School, Kaliabu, there are already available facilities for students in the health sector with the existence of Islamic Boarding School Health Posts or often referred to as Poskestren. The purpose of the service is to study and analyze the capacity building of the Mamba'ul Huda Kaliabu's poskestren organization. The approach used in this study is ABCD. ABCD is used in this service because it is considered appropriate to solve problems according to the assets owned by certain groups or institutions. The method used in this service is by holding deliberation, mentoring, and training with the  management of the Mamba'ul Huda poskestren. The results of the service can be concluded that the capacity building of the Mamba'ul Huda Kaliabu poskestren organization has developed well in health services, but in organizing and increasing the knowledge of Husada students it still requires supervision, training in the fields of organization, leadership, and  skills of Husada students. The author hopes that after this service, they can develop the insight of Husada students in managing the Mamba'ul Huda Poskestren